The Birth of English: Exploring the Characteristics of Old English and the role of Anglo-Saxon in its Evolution - Rani, Hena Lutfia; Faustina, Lintang Widya; Nurdiansyah, Lola; Sanukerti, Yunda Refia Atma (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
English is a universal language that most countries use for international communication. English has had numerous impacts that have changed the old English, which has turned into the modern English we use now. In the beginning, English was influenced by Celtic, and then Germanic influences came with the colonization by three big clans: Angles, Saxons, and Jutes. In that case, the purpose of this research on Old English characteristics is to understand more about the history and evolution of the English language from the 5th to 11th centuries (Old English) and continuing until the 16th century (modern English). Thus, readers could effectively study and preserve the history of the birth of English. The method used in this research article is the qualitative method with phenomenon analyzation. This method is used to find out the changes in the English language from the characteristics, including pronunciation, present vocabulary, and grammar. Besides that, this research is also done to discover the influence of AngloSaxons. Writers accomplished a deeper research through trusted sources such as “History of the English Language 5th Edition” by Albert C. Baugh and Thomas Cable. After going through the research and further study, it could be said that English has experienced a significant evolution. Starting from structure and language patterns to usage case and inflection. The English language we know now has become more concise and organised. The English language (Modern English) has become simpler with only 34.000 words, and it is easier to learn as a second language.